Key Factors in Technology Adoption Processes - Hoyos Muñoz, Joiner Alexander (2022)
Technological  development  accompanies  the  progress  of  human  civilizations  and  is  closely related to their social and cultural characteristics. Currently, the rise of technology and, especially, of information and communication technologies determines to a large extent  the  way  in  which  we  relate  to  each  other  and  how  we  approach  aspects  such  as  politics,  economics  and  education,  among  others.  In  the  organizational  context,  technology is an indicator of the degree of maturity and competitiveness of companies and provides them with the capacity to respond to market demands and be sustainable over  time.  However,  it  is  notorious  in  organizations  that individuals  exhibit  resistance  to the introduction and use of technologies, which means that the expected results do not materialize. In this context, the present work arises with the objective of compiling the  constructs  that  have  been  identified  in  the  theories  and  acceptance  models  as  relevant aspects that determine the use of technology by people. The methodological approach is exploratory, with a qualitative design and the use of secondary information. The methodology is carried out through 3 stages: first, the planning of the technological surveillance  in  which  the  key  factors  of  surveillance,  the  construction  of  the  search  equation  and  the  sources  of  information  are  defined;  secondly,  the  development  of  technological surveillance in which searches are carried out in databases; and, thirdly, the consolidation and validation of the results. The work allows us to conclude that the attitude towards technology, the perceived usefulness and the perceived ease of use are the constructs that underlie most of the models and theories on technology adoption.